Politicians' motivation, political culture, and electoral competition - Klaas J. Beniers; Robert Dur (Center for Economic Studies and ifo Institute (CESifo), 2004)
We study electoral competition among politicians who are heterogeneous both in competence and in how much they care about (what they perceive as) the public interest relative to the private rents from being in office. We show that politicians? incentives to behave opportunistically increase with politicians? pay and with polarization of policy preferences. Moreover, politicians may have stronger incentives to behave opportunistically if other politicians are more likely to behave opportunistically. A political culture may therefore be selfreinforcing and multiple equilibria may arise. Lastly, we show that the mere probability that politicians care about the public interest enables opportunistic politicians to damage the reputation of their competitors. Consequently, efficient policies may be reversed.
Keywords: D78; D72; 330; politicians' motivation; politicians' pay; political culture; electoral competition; coalition governments; reputation bashing; Politiker; Motivation; Politische Kultur; Wahlkampf; Public Choice; Theorie